2020
DOI: 10.30597/mkmi.v16i2.9090
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Alat Pelindung Diri dan Keracunan Pestisida pada Pekerja di Perusahaan Penyemprot Hama

Abstract: Industri jasa pest control merupakan salah satu industri dibidang jasa pengendalian hama, terutama yang ada di daerah pemukiman yang menggunakan pestisida yang dapat membahayakan terutama bagi penyemprot hama. Tujuan penelitian untuk mengetahui penggunaan alat pelindung diri (APD) dengan keracunan pestisida pada pekerja di perusahaan penyemprot hama, Penelitian ini menggunakan desain cross sectional dengan sampel sebanyak 30 orang penyemprot hama di PT Zeta Prima Lestari dengan metode total sampling. Analisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Hansen et al, (2020) found that organophosphate and carbamate pesticides can inhibit the acetylcholinesterase activity of farmers in Uganda, causing blood glucose to increase significantly. Various factors cause farmers pesticide poisoning, including the use of personal protective equipment, service life, length of spraying, type of pesticide, and pesticide management (Istianah and Yuniastuti, 2017;Santoso et al, 2019;Yogisutanti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al, (2020) found that organophosphate and carbamate pesticides can inhibit the acetylcholinesterase activity of farmers in Uganda, causing blood glucose to increase significantly. Various factors cause farmers pesticide poisoning, including the use of personal protective equipment, service life, length of spraying, type of pesticide, and pesticide management (Istianah and Yuniastuti, 2017;Santoso et al, 2019;Yogisutanti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%